Effect of displaced versus non‐displaced pelvic fractures on long‐term racing performance in 31 Thoroughbred racehorses. Issue 6 (26th April 2013) - Hennessy, SE; Muurlink, MA; Anderson, GA; Puksmann, TN; Whitton, RC
<x xml:space="preserve">Abstract</x> Objective To evaluate the long‐term racing prognosis for Thoroughbred racehorses with displaced versus non‐displaced fractures of the pelvis identified by scintigraphy. Design Retrospective case analysis. Methods Medical records of 31 Thoroughbred racehorses presenting to the University of Melbourne Equine Centre with fractures of the pelvis that were identified by scintigraphy were reviewed. Pelvic fracture site was determined and defined as displaced or non‐displaced based on ultrasound and/or radiographic findings. Race records were analysed for each horse, with a minimum of 24 months' follow‐up, and correlated with fracture type to determine long‐term prognosis for racing. Results are expressed as median and range. Results Fractures at a single site were more common (n = 22) than fractures involving two sites (n = 9) and the ilial wing was the most commonly affected (n = 12). Thoroughbred racehorses with displaced pelvic fractures at any site (n = 12) raced fewer times within 24 months of diagnosis than horses with non‐displaced fractures (n = 19) (median 0.5, range 0–13 vs 7, 0–24; P = 0.037), but there was no clear statistical difference in race earnings between the two groups (median A$0, range A$0–$123, 250 vs A$14, 440, A$0–$325, 500, respectively; P = 0.080). Four horses with displaced fractures (33%) were euthanased on humane grounds because of persistent severe pain. When these horses were excluded from the analysis, there were no differences in performance variables between horses with a displaced or non‐displaced pelvic fracture. Conclusion Thoroughbred racehorses with a displaced or non‐displaced pelvic fracture that survive the initial post‐injury period have a good prognosis for racing.